Discovery and Characterization of the Biflavones From Ginkgo biloba as Highly Specific and Potent Inhibitors Against Human Carboxylesterase 2 - Song, Yun-Qing; He, Rong-Jing; Pu, Dan; Guan, Xiao-Qing; Shi, Jin-Hui; Li, Yao-Guang; Hou, Jie; Jia, Shou-Ning; Qin, Wei-Wei; Fang, Sheng-Quan; Ge, Guang-Bo (Frontiers in Pharmacology, 2021)
Human carboxylesterase 2 (CES2), one of the most abundant hydrolases distributed in the small intestine, has been validated as a key therapeutic target to ameliorate the intestinal toxicity caused by irinotecan. This study aims to discover efficacious CES2 inhibitors from natural products and to characterize the inhibition potentials and inhibitory mechanisms of the newly identified CES2 inhibitors. Following high-throughput screening and evaluation of the inhibition potency of more than 100 natural products against CES2, it was found that the biflavones isolated from Ginkgo biloba displayed extremely potent CES2 inhibition activities and high specificity over CES1 (>1000-fold). Further investigation showed that ginkgetin, bilobetin, sciadopitysin and isoginkgetin potently inhibited CES2-catalyzed hydrolysis of various substrates, including the CES2 substrate-drug irinotecan. Notably, the inhibition potentials of four biflavones against CES2 were more potent than that of loperamide, a marketed anti-diarrhea agent used for alleviating irinotecan-induced intestinal toxicity. Inhibition kinetic analyses demonstrated that ginkgetin, bilobetin, sciadopitysin and isoginkgetin potently inhibited CES2-catalyzed fluorescein diacetate hydrolysis via a reversible and mixed inhibition manner, with Ki values of less than 100 nM. Ensemble docking and molecular dynamics revealed that these biflavones could tightly and stably bind on the catalytic cavity of CES2 via hydrogen bonding and π-π stacking interactions, while the interactions with CES1 were awfully poor. Collectively, this study reports that the biflavones isolated from Ginkgo biloba are potent and highly specific CES2 inhibitors, which offers several promising lead compounds for developing novel anti-diarrhea agent to alleviate irinotecan-induced diarrhea.